Economic effects of EU Eastern expansion: High growth in the new member economies with a continuing prosperity gap - Ognian N. Hishow (Stiftung Wissenschaft und Politik (SWP), 2004)
The EU enlargement to the East resulted in a dramatic core-periphery income gap: real GDP per capita in East Central Europe (ECE) is up to 60 percent lower than in the EU 15. However, as capital mobility is no longer hindered, investment will flow from capital-rich western Europe to the capital-poor ECE, where it will ensure the expansion of capital stock per worker and thus lead to productivity growth. The effect will be a gradual East-West convergence of input and output prices, including wages, and this even without labor mobility.As for Germany, German capital will continue to flow to the new member countries. To date net flows of less than one percent of German GDP per year have been recorded. There has only been a minimal slackening of growth and a slight loss of jobs. In economic terms moving production to Eastern Europe makes sense. This is because the average investment needed per job in the former EU-15 is around EUR 60,000 and thus the fourfold the respective amount in ECE. Outsourcing will therefore most likely continue.Furthermore, the new EU members will continue to be net receivers of transfers from Brussels while Germany will be a net contributor for some time. Germany's payments reduce its domestic demand and impede its growth. Particularly in times of very low growth rates this effect is noticeable. A reduction of the German net transfer to Brussels would be, ceteris paribus, advantageous from a national point of view.As the ECE economies enjoy higher growth rates than the EU 15, it would be unwise to slow down the process of real convergence by excessive demands for tax harmonization. Such harmonization might bring short-term advantages to the countries and economies of the EU-15, but they would be more than neutralized by the effect of slowing down the ECE countries in their efforts to catch up economically. (SWP-Research Papers / SWP)
Keywords: 320